CASEL and Good Governance-Based Integrative Japanese Language Learning Model to Build Character in Vocational Training Institution (LPK) Students - Jeine Wahani, Yenny; Toda, Akira; Bintang Pratiwi Harahap, Putri (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This quasi-experimental study evaluates the effectiveness of an integrative Japanese language learning model based on CASEL (Collaborative for Academic, Social, and Emotional Learning) and Good Governance principles in enhancing character development of Vocational Training Center (LPK) students, preparing Indonesian workers for global workplace challenges. Employing a pre-test and post-test design, 40 LPK students were randomly assigned to experimental (n=20) and control (n=20) groups. The experimental group received Japanese language instruction integrating SEL and Good Governance elements, while the control group underwent conventional learning. A validated instrument measured five CASEL competencies: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making. Data were analyzed using paired t-tests, independent t-tests, ANCOVA, and MANOVA. The experimental group achieved a mean gain score of 25.7 points versus 6.3 points in the control group, demonstrating highly significant differences (t = 8.952, p < 0.001) with a very large effect size (Cohen's d = 2.83). MANOVA revealed significant improvements across all CASEL dimensions, with self-management showing the greatest enhancement (F = 22.73, p < 0.001, η² = 0.374). The intervention proved four times more effective than conventional methods (improvement ratio 4.1:1), with 70% of experimental participants achieving high improvement levels compared to only 5% in the control group.This study provides the first empirical evidence integrating CASEL and Good Governance within Japanese language learning in Indonesian vocational settings. Unlike previous research treating language and character development separately, this investigation establishes a holistic model leveraging culturally rich Japanese content as an authentic medium for character value internalization, directly addressing workforce development needs for workers combining linguistic competence with strong ethical foundations required in global workplaces.